Comparison of seven fall risk assessment tools in community-dwelling Korean older women. Issue 3 (4th March 2017) - Kim, Taekyoung; Xiong, Shuping
Abstract: This study aimed to compare seven widely used fall risk assessment tools in terms of validity and practicality, and to provide a guideline for choosing appropriate fall risk assessment tools for elderly Koreans. Sixty community-dwelling Korean older women (30 fallers and 30 matched non-fallers) were evaluated. Performance measures of all tools were compared between the faller and non-faller groups through two sample t -tests. Receiver Operating Characteristic curves were generated with odds ratios for discriminant analysis. Results showed that four tools had significant discriminative power, and the shortened version of Falls Efficacy Scale (SFES) showed excellent discriminant validity, followed by Berg Balance Scale (BBS) with acceptable discriminant validity. The Mini Balance Evaluation System Test and Timed Up and Go, however, had limited discriminant validities. In terms of practicality, SFES was also excellent. These findings suggest that SFES is the most suitable tool for assessing the fall risks of community-dwelling Korean older women, followed by BBS. Practitioner Summary : There is no general guideline on which fall risk assessment tools are suitable for community-dwelling Korean older women. This study compared seven widely used assessment tools in terms of validity and practicality. Results suggested that the short Falls Efficacy Scale is the most suitable tool, followed by Berg Balance Scale.